Evolutionary Computing Techniques for Resolving Load Dispatch Problem - Raj, Jennifer S. (Journal of Soft Computing Paradigm, 2020)
To have an effective scheduling of the generators in order to achieve a perfect planning and functioning of the electric power generation system so as to satisfy the demands required, the economic load dispatch is important. The economic load dispatch is very essential in the network operations in the market with the derestricted electricity and takes a vital role in the power plant operations. ELD problem scopes to meet the load demands fulfilling the various constraints in the operation and minimizing the cost of the operations. The conventional methods put forth to find the solution were found unsuitable as the cost curves of the units were assume to be uneventfully increasing linear functions and whereas the practical systems are nonlinear. So the evolutionary computing engaging the GA in combination with the PSO to resolve the economic load dispatching problem
Keywords: Load Dispatching Problem; Cost Optimization; Evolutionary Computing; Genetic Algorithm and Particle Swarm Optimization